2014
DOI: 10.1063/1.4878404
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene film on metal surface: Diffusion of metal atoms and interface model

Abstract: We try to understand the fact that fullerene film behaves as n-type semiconductor in electronic devices and establish a model describing the energy level alignment at fullerene/metal interfaces. The C60/Ag(100) system was taken as a prototype and studied with photoemission measurements. The photoemission spectra revealed that the Ag atoms of the substrate diffused far into C60 film and donated electrons to the molecules. So the C60 film became n-type semiconductor with the Ag atoms acting as dopants. The C60/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…11 In addition, higher temperature facilitates Ag diffusion in C 60 . 10 These studies coupled with the fact that C 60 , BCP, and Ag are deposited by thermal evaporation in this study indicates the possibility of Ag diffusion within the ETL materials to form the C 60 + BCP + Ag physically mixed layer. To avoid the formation of the C 60 + BCP + Ag physically mixed layer and improve device performance, Ag deposition techniques and conditions that lead to limited Ag diffusion should be considered.…”
Section: ■ Results and Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…11 In addition, higher temperature facilitates Ag diffusion in C 60 . 10 These studies coupled with the fact that C 60 , BCP, and Ag are deposited by thermal evaporation in this study indicates the possibility of Ag diffusion within the ETL materials to form the C 60 + BCP + Ag physically mixed layer. To avoid the formation of the C 60 + BCP + Ag physically mixed layer and improve device performance, Ag deposition techniques and conditions that lead to limited Ag diffusion should be considered.…”
Section: ■ Results and Discussionmentioning
confidence: 56%
“…It has been studied that Ag diffuses up to 20 nm in BCP and forms a Ag + BCP complex, in which case electron transport takes place through the Ag + BCP complex rather than through the intact bulk BCP layer in solar cells . In addition, higher temperature facilitates Ag diffusion in C 60 . These studies coupled with the fact that C 60 , BCP, and Ag are deposited by thermal evaporation in this study indicates the possibility of Ag diffusion within the ETL materials to form the C 60 + BCP + Ag physically mixed layer.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Hetero-epitaxial film in atomic-scale structure had been investigated by SXRD and LEED analysis [39,40], and the inelastic-mean-free-path of the Bi 4f 7/2 photoelectron at kinetic energy 338 eV was estimated to be ~9 Å [41]. With these initial conditions a series of photoelectron attenuation values for the two chemical environments can be estimated using the peaks' intensity and then eventually the Bi coverage can be obtained [42]. Specifically, when the two peaks have nearly equal intensity the deposited Bi reaches a single bilayer, which is also cross-checked by the quartz microbalance flux monitor.…”
Section: Methodsmentioning
confidence: 99%
“…It should be also mentioned that the molecule layer was more rmly bonded to the surface than the molecules above the rst layer, as we will discuss later. The molecules above the rst layer are considered to be chemically pristine fullerenes (though, when the applied eld is present, they may be partially charged and/or have a dipole moment) because previous studies have revealed that the electronic properties of molecules above the rst layer are the same as that of the pristine C 60 , which was true for various metal substrates, including tungsten [18][19][20]. Hence, we call the rst layer a buffer layer to distinguish it from the other layers.…”
Section: Experimental: Summary Of Characteristic Fem Images and Our I...mentioning
confidence: 99%